2009
DOI: 10.1002/app.31502
|View full text |Cite
|
Sign up to set email alerts
|

Thermal pressure coefficient of a polyhedral oligomeric silsesquioxane (POSS)‐reinforced epoxy resin

Abstract: ABSTRACT:The thermal pressure coefficients of a neat, unfilled, epoxy resin and a 10 wt % POSS (polyhedral oligomeric silsesquioxane)-filled epoxy nanocomposite have been measured using a thick-walled tube method. It is found that just below the glass transition temperature the thermal pressure coefficient is $ 20% smaller for the polymer composite containing 10% POSS than for the neat, unfilled resin. The thermal expansion coefficient and thermal pressure coefficient of the uncured POSS itself are also report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
3
1
Order By: Relevance
“…This differs from results on a 10 wt % POSS nanoparticle/epoxy system where 10 and 20% reductions in the thermal stress coefficient (as estimated by a P G) and thermal pressure coefficient c at 10 wt % POSS loading were found 4,5 in the glassy state below T g.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…This differs from results on a 10 wt % POSS nanoparticle/epoxy system where 10 and 20% reductions in the thermal stress coefficient (as estimated by a P G) and thermal pressure coefficient c at 10 wt % POSS loading were found 4,5 in the glassy state below T g.…”
Section: Discussioncontrasting
confidence: 79%
“…[1][2][3][4] One potential strategy to mitigate thermal residual stresses in fiber-reinforced polymeric materials may be to add nanoparticles to the polymer matrix. 4,5 Although moduli and thermal expansivities normally exhibit a reciprocal relationship, [6][7][8] findings for a 10 wt % polyhedral oligomeric silsesquioxane (POSS)-reinforced epoxy resin show reductions in the thermal pressure coefficient and the thermal stress coefficient (the product of linear thermal expansion coefficient a L and Young's modulus E). 4,5 In addition, model calculations have also reported polymer nanocomposites may have exceptional properties-for example, the incorporation of nanoparticles may reduce the bulk modulus of the neat polymer.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Figure 5 shows calculations of K B normalized to its pure polymer melt analog, K B0 , over a wide range of interface attraction strengths. At higher " pc , where adsorbed layers are well-developed and polymers mediate repulsive interparticle interactions, K B decreases with increasing c , consistent with prior theoretical studies [18,23] as, seemingly, a recent measurement of the thermal pressure coefficient (proportional to K B ) in a polymer nanocomposite [24]. However, for FIG.…”
supporting
confidence: 74%
“…These were reviewed by Li et al in 2001. Since then, Win et al have shown that addition of 10 wt % POSS reduces the thermal pressure coefficient of an epoxy-diamine thermoset, thereby improving its mechanical properties on thermal cycling, and others have shown that incorporation of small amounts of POSS into epoxy-amine/anhydride mixtures, either as pendant groups or as reactants, improves flame retardency, , elasticity, , dielectric, , physical aging, and related properties. It has been found that in some cases POSS increases the glass–liquid transition temperature of the nanocomposites, and decreases it for others. ,, Kinetics of polymerization of POSS-containing mixtures has also been studied.…”
Section: Introductionmentioning
confidence: 99%